Modelling and Analysis using The Thyristors Controlled Series Compensators for Electrical Power Systems - ZAKRI, AZRIYENNI AZHARI; SIREGAR, TAUFIQ RAHMAN; MUSTAFA, MOHD WAZIR; SUNANDA, WAHRI (Institut Teknologi Nasional, Bandung, 2023)
ABSTRAKUntuk memastikan bahwa kebutuhan masyarakat yang berkembang terpenuhi dan tingkat ketergantungan sistem cukup, sangat penting untuk mengelola dan memelihara sistem distribusi daya yang andal. Karena jarak transmisi yang jauh, tidak mungkin untuk mencegah kerusakan instalasi pada sistem tenaga listrik. Hal ini berdampak signifikan pada transmisi tenaga listrik, yang mengakibatkan penurunan tegangan dan hilangnya energi listrik. Penggunaan Flexible Alternating Current Transmission System (FACTS) merupakan salah satu cara untuk mengurangi ketidakstabilan tegangan dan meningkatkan kehandalan jaringan tenaga listrik. Perangkat FACTS adalah Thyristor Controlled Series Compensator (TCSC). Kapasitas daya saluran transmisi ditingkatkan dengan menambahkan TCSC secara seri dengan saluran transmisi. Untuk meningkatkan aliran daya, reaktansi TCSC dapat disesuaikan untuk memodulasi reaktansi saluran transmisi.Kata kunci: sistem tenaga listrik, FACTS, kompensator seri, tiristor, TCSCÂ ABSTRACTIn order to ensure that the expanding requirements of the community are met and that the system's level of dependability is sufficient, it is crucial to manage and maintain a reliable power distribution system. Due to the extensive transmission distance, it is impossible to prevent installation malfunctions in the electric power system. This has a significant impact on the transmission of electric power, resulting in a voltage decrease and a loss of electrical energy. Using a Flexible Alternating Current Transmission System (FACTS) is one way to reduce voltage instability and improve the dependability of the electrical power grid. A FACTS device is the Thyristor Controlled Series Compensator (TCSC). The power capacity of the transmission line is increased by adding the TCSC in series with the transmission line. In order to increase power flow, the TCSC's reactance can be adjusted to modulate the transmission line's reactance.Keywords: electrical power system, FACTS, series compensators, thyristors, TCSC